Alternative Techniques for Animal Fat Authentication Based on Microscopic Crystal Pattern and Fatty Acid Composition Using Gas Chromatography-Mass Spectrometry (GC-MS) - Dewi, Diana Candra; Mahdi, Chanif; Sulistyarti, Hermin; Aulanni`am, Aulanni`am (The Journal of Pure and Applied Chemistry Research, 2024)
Fat authentication is strongly required for the reason of religious food ethics, human health, and preferences. This research reported two simple techniques approach for recognizing fat based on the character of microscopic and physicochemical properties of fat extractedusing different polarity solvents. The formation of microcrystals as well as fatty acid composition were investigated by involving variables of four different types of animal fat and three different solvents. Theisolate fats were directly crystallized under incubation at room temperature and observedusing an optical microscope while fatty acid composition was determined by hydrolyzing and trans-esterifying fat samples before analysis using GC-MS. The microscopic structures of the obtained crystals areneedle-basedwitharadial orientation in spherulitic pattern which characteristic to each type of fat. The lard fat crystal was authentically distinguished from its shape of a partially radial fan, whilst the shape of fat crystals from beef, goat, and lamb are needle-shaped with a full radialorientation. Fatty acids obtained from all types of fats and types of solvents show similar types but different abundances, the main saturated fatty acids are palmitate, stearate myristic and the main unsaturated fatty acids are oleic, palmitoleic, and linoleic. Gas chromatography-mass spectrometry (GC-MS) analysis exhibited that lard composed higher Î£USFA compared to Î£SFA but other fats (tallow, goat, and lamb) showed converse behavior.